Morphological and physiological responses of CMD resistant cassava (Manihot esculenta) genotypes to nutrient regimes (Current Horticulture, 2023)
The field studies were carried out on cassava ( Manihot esculenta Crantz) varieties resistant to cassava mosaic disease (V1-CR43-2,  V2-15 S 59, V3-15 S 409 , V4-15 S 154, V5-CR43-7, V6-8S 501-2, V7-CR24-4, V8- 15S-436) and three levels of nutrient doses (F1-75:50:75,  F2- 100:50:100 and F3- 125:50:125 kg NPK/ha) in spilt plot design during 2018-19 and 2019-20 to assess the response of varieties to  nutrition. There was significant difference in morphological and physiological parameters among varieties, but not with different  nutrient doses. The rate of leaf production was more 4-6 months after planting (34-40%) and percentage retention was less for first  season crop (55.6-41.4%) compared to second season (77.2-52.5 %). Though not significant, higher nutrition levels recorded more  number of green leaves as well as leaf area at most of the stages. Tuber bulking rate was 0.19 to 0.37 g/day during initial two months.  The rate increased and maximum bulking was recorded between 4 and 8 months (2.15-6.71 g/day). Pooled analysis also showed a  gradual increase in tuber yield with nutrient levels, but was not significant (7%). The varieties responded differently to nutrients  with respect to tuber yield. F3 recorded higher tuber yield (66.9 t/ha) than F1 (45.7 t/ha) in V7 and V6 recorded highest tuber yield with  F2 level of nutrition (71.1 t/ha). F1 was found optimum for rest of the varieties.
Keywords: Leaf area index; Nutrition; Tuber bulking rate; Tuber yield; Varietal response